After the End of Theory. Why do Cultural Studies need to be Reinvented? - Ilnicki, Rafał (Journal of Applied Cultural Studies, 2015)
Contemporary humanities are confronted with a search for new forms of legitimization. Processes that enforce such a necessity stem from the technicization of contemporary culture. The methodologies of the humanities, and even their status as a group of academic disciplines, are questionable. The aim of the article is to argue that these external and internal problems in the humanities are interlinked with the state of being after the end of theory. This assumption is grounded on the thesis that the humanities need to find a solution to the impasse which could be described as the questions of what theory means and why society should be concerned about it.